Improving Students' Understanding of Islamic Education Learning through the Contextual Teaching and Learning Method at SD Islam Terpadu Nurul Ishlah Banda Aceh - Jihad, Zaghlul; Supiani, Erna (Journal of Indonesian Primary School, 2025)
This study aims to describe the learning process using the Contextual Teaching and Learning method for the material Welcoming the Age of Puberty in grade IV students of SDIT Nurul Ishlah Banda Aceh in improving their understanding. This study was conducted in 2 cycles. The first cycle consists of 2 learning activities. Likewise with the second cycle, but using different treatments. Each cycle will have planning, implementation, observation, and reflection activities. The research subjects taken were grade IV students of SDIT Nurul Ishlah Banda Aceh, totaling 100 students. In this case, the author conducted research on the Learning Group (Rombel) class IV-C, with a total of 33 students. Where 17 women and 16 men. The data analysis technique is qualitative. The results of the study showed that the Contextual Teaching and Learning method for the material Welcoming the Age of Puberty in grade IV students of SDIT Nurul Ishlah Banda Aceh has increased. Before the study was conducted, the percentage of their understanding achievement was 50%. After the research in cycle I, it increased to 72%, this means there was an increase of 22%, while in cycle II it had reached 90%. Thus, this research has met the desired target of at least 75%. Thus, the use of the contextual teaching and learning model can be used as an alternative in Islamic education learning so that students can understand the concepts.